Hubungan Antara Job Strain Dengan Terjadinya Infark Miokard Pada Pasien Pusat Jantung Nasional - Rima Melati; Endang Basuki; Budhi Setianto (The Indonesian Heart Association, 2008)
Background. Coronary heart disease is the most frightening disease and still become a problem in the developed and developing countries. The prevalence of myocardial infarction is also increasing from year to year. Beside the conventional risk factors, it is also influenced by occupational factors. Although job strain can cause stress which would have impact on the occurence of myocardial infarction, the prevention strategies being implemented are just for conventional risk factors. There is still no concern for occupational factors which can also cause job strain. This study was aimed to assess the relationship between job strain and other risk factors with myocardial infarction among workers.Methods. The study design was matched case – control 1:1 for age. Data were collected by using general questionnaire which covered demography characteristics, conventional risk factors, job characteristics, and demand – control questionnaire (JCQ) to assess job strain.Result. Job strain, smoking and dyslipidemia were risk factors which had relationship with myocardial infarction. Job strain increased myocardial infarction risk by 6.8 times (Adj OR 6.80, 95% CI: 2.72 ; 16.98, p = 0.000). Light smokers increased myocardial infarction risk by 15 times (Adj OR 14.97, 95% CI: 3.17 ; 70.74, p = 0.001), medium smokers increased myocardial infarction risk by 7.7 times (Adj OR 7.72, 95% CI: 2.73 ; 21.84, p = 0.000), and heavy smokers increased myocardial infarction risk by 26 times (Adj OR 25.61, 95% CI: 5.25 ; 124.88, p = 0.000). Dyslipidemia increased myocardial infarction risk by 2.8 times (Adj OR 2.82, 95% CI: 1.07 ; 7.44, p = 0.035). Job strain component which increased myocardial infarction risk was high job demand (Adj OR 2.44, 95% CI: 1.02 ; 5.85, p = 0.046).Conclusion. Job strain, smoking and dyslipidemia simultaneously had relationship with myocardial infarction.